A comparative study to evaluate the linear dimensional change and compression resistance of four elastomeric interocclusal recording materials: An in vitro study - Tapan K Giri; Saurav Banerjee; Tridib N Banerjee; Bidhan C Mandal; Piyush Dongre; Palak Khanna; Debanti Giri (Wolters Kluwer Medknow Publications, 2024)
The transfer of interocclusal data from the patient's mouth to articulators utilizing various types of recording media is necessary for the production of dental prostheses. Occlusal errors in the final prosthesis result from any discrepancies in these interocclusal records. Materials and Methods: The purpose of this study was to assess the linear dimensional changes in the four elastomeric interocclusal recording materials as well as the material's resistance to compression during the cast mounting on the articulator. Result: All four elastomeric materials showed decreasing stability over time and 2 mm thickness showed the highest compression resistance with minimal articulation error. Conclusion: Dimensional stability depends on material and time factors, and compressive resistance decreases with increasing thickness.